Plant performance and survival across transplant experiments depend upon temperature and precipitation change along elevation. (3rd April 2020) - Midolo, Gabriele; Wellstein, Camilla
Abstract: Understanding how plant individuals perform in non‐local sites is key in the context of contemporary range shifts along elevation. Transplant experiments conducted in mountain ecosystems are rising as key tools to measure the intraspecific response of individuals transplanted across contrasting elevations. However, a synthesis quantifying patterns of plant performance in response to changes in abiotic factors across different species and mountain ranges is still lacking. We conducted a meta‐analysis to quantitatively summarize patterns of plant species' performance variation in response to changes in temperature and precipitation within their elevation range across multiple transplant experiment studies. We compiled a dataset obtained from 38 studies and 49 vascular plant species in total addressing intraspecific performance variation in terms of survival, germination, biomass, height, number of vegetative organs, number of reproductive units, SLA and leaf size. We both compared pairs of transplanted individuals to those growing at their site of origin ('away vs. home') and to the local individuals found at the site of transplant ('foreign vs. local'). Overall, individuals transplanted downward showed larger biomass and height compared to their site of origin but failed to adjust these traits and survival to that of local individuals. Individuals transplanted upward adjusted their traits by decreasing plant growth and number of reproductive units to that of local individuals but showed lower survival. Importantly, changes in survival, biomass, height, leaf size, number of vegetative organs and reproductive units increased linearly with the difference in mean annual temperature between site of transplant and site of origin in the 'away vs. home' comparison. Conversely, changes in biomass, leaf size, number of vegetative organs and reproductive units increased with mean annual precipitation difference between sites in the 'foreign vs. local' comparison. Synthesis . We detected common trends in survival and intraspecific trait variation across different species and transplant experiments conducted along elevational gradients. Because plasticity and adaptation play a crucial role in plant shift, establishment and persistence under non‐local environmental conditions, our meta‐analysis contributes to better understand how rapid plant shifts are constrained by climatic conditions within species' elevational range. Abstract : We detected common trends in survival and intraspecific trait variation across different species and transplant experiments conducted along elevational gradients. Because plasticity and adaptation play a crucial role in plant shift, establishment and persistence under non‐local environmental conditions, our meta‐analysis contributes to better understand how rapid plant shifts are constrained by climatic conditions within species' elevational range.